The Third-Generation Armenian American Writers Echo the Quest for Self-Identity with the Genocide at Its Core - Peroomian, Rubina (Armenian Folia Anglistika, 2012)
The article presents the strife of numerous American writers of Armenian origin to identify their roots by literary portrayal of the tragic fate of the survivors of the Armenian Genocide. These stories, which are written in English, bear the cultural, religious, social-political impact that are typical of already the third generation of the Genocide survivors. However, all of them are based on the great tragedy of the Armenian Genocide and its continual refusal.